A Systematic Literature Review on the Relationship Between Human Character, Key Employee Indicators, and Outstanding Performance in Organizational University Context - Saleh, Nursahdi; Sain, Muhammad (International Conference On Economics Business Management And Accounting (ICOEMA), 2025)
This systematic literature review explores the integration of human character development and Key Performance Indicators (KPIs) in enhancing organizational performance, specifically within higher education institutions. The study investigates how emotional intelligence, ethical leadership, and personal traits influence academic outcomes and institutional success. Through an analysis of selected articles published between 2020 and 2025, it was found that human character attributes, such as self discipline and integrity, play a significant role in boosting employee performance and satisfaction. Furthermore, KPIs, when aligned with personal development, have a more substantial impact on organizational outcomes than when used in isolation. The findings highlight the importance of integrating both human character and KPIs into performance management systems to create a positive organizational culture and improve academic performance. Universities, particularly in underdeveloped regions, must adopt a holistic approach to performance management that includes both quantitative metrics and personal development strategies to foster long term growth and competitiveness.